A multimodal analysis of the representation of voter disillusionment in social media memes distributed on Twitter in the lead up to the 2019 South African general election - Jeftha, Courtney Alexandra (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study is situated in the context of the 2019 South African general election, which saw the lowest voter turnout since its first democratic election in 1994. Many have questioned the capabilities of the African National Congress (ANC) since they came into power in 1994, due to allegations of corruption, maladministration and poor leadership. The concerns about the party's ability to manage the country's various social issues have led to a drop in voter turnout. There was much discussion in the media about the lack of voter turnout amongst young people in South Africa. This topic became a trending topic on social media under the #iwanttovotebut hashtag. The sentiments expressed by South African Twitter users in the #iwanttovotebut memes are explored in this study. The analysis of the memes draws on the works of Kress and van Leeuwen's (1996; 2006) visual social semiotics, Fairclough's (1989) approach to Critical discourse analysis (CDA), and Thompson's operation of ideologies. VSS allows for the description of the various semiotic resources that memers use to construct their meaning from multimodal texts. The tools provided by CDA go beyond the description of VSS and develop a more detailed analysis of how the memers construct their discourses of democracy/governance. Thompson's (1991) approach to understanding how ideology operates in language enables the deepening of the understanding of the dominant and naturalised notions of democracy/governance. The findings indicate that memers have a limited understanding of democracy. They also have a limited understanding of how political parties operate and their responsibilities in the form of government and various agencies. In addition, it is not surprising that young people are not voting in the 2019 general election. This is a phenomenon that the media has characterized as "apathy." However, this research indicates that it would be more accurate to describe it as "disillusionment."
Keywords: Elections -- South Africa 21st century; Culture-- Study and teaching -- South Africa; Mass media-- Study and teaching -- South Africa; Social media -- South Africa; Memes -- South Africa; Visual sociology; Textual Analysis; Critical discourse analysis; Modality (Linguistics)